Determinants of platform ecosystem health: an exploration based on grounded theory - Chen, Yun; Sun, Yaowu (Journal of Business Economics and Management, 2021)
Whether the platform ecosystem operates well influences the survival and development of all actors. Drawing on the literature of business ecosystem health, we propose the topic of platform ecosystem health, which refers to a stable and sustainable operating status obtained through cooperation among actors that can effectively respond to turbulent changes, meet market demand, and make profit. Platform ecosystem health is complexly influenced by internal and external factors, and exploring these is the first step towards its improvement. To address this question, this study uses grounded theory to identify the main determinants and theoretically explain the ways in which these determinants influence platform ecosystem health. Specifically, we select 15 representative platform ecosystems in the mobile communication services, e-commerce, and high-tech manufacturing industries using theoretical sampling. Three encoding processes and theoretical saturation tests are then employed to analyze interview and secondary data on the health of these platform ecosystems. Based on the identified 132 concepts and nine categories, we obtain four types of determinants: dominant capabilities of the platform enterprise, cooperation potential of the complementary enterprise, products and services, and industry environment. We finally propose four propositions to illustrate the relationships between the determinants and platform ecosystem health.